2019
DOI: 10.1088/1755-1315/286/1/012032
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Condominium Property Value Uplift around Light Rail Transit Stations Using a Hedonic Pricing Model

Abstract: This paper aims to investigate the impact of proximity to the nearest light rail transit station on the value of condominium properties in Greater Kuala Lumpur, Malaysia. The paper utilizes a data set of 476 condominium sales occurring in Greater Kuala Lumpur between January 2017 and the second quarter of 2018. Using a hedonic pricing model, housing price was modelled as a function of proximity to the nearest light rail transit station and with regard to other structural and locational attributes. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
2
3
0
Order By: Relevance
“…The apartment prices increased as the distance to the CBD decreased. This result aligns with many studies that have attempted to estimate housing prices in the CBD [44,45,[51][52][53][54]. A study analyzing housing price determinants in Beijing, China Duan et al [40] claimed that housing prices are higher because of supply shortages in downtown areas, where land use regulations are strict and developable land is relatively scarce.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The apartment prices increased as the distance to the CBD decreased. This result aligns with many studies that have attempted to estimate housing prices in the CBD [44,45,[51][52][53][54]. A study analyzing housing price determinants in Beijing, China Duan et al [40] claimed that housing prices are higher because of supply shortages in downtown areas, where land use regulations are strict and developable land is relatively scarce.…”
Section: Discussionsupporting
confidence: 74%
“…In general, housing prices appear to decrease as the distance to the CBD increases. This shows mostly the same results regardless of the study area [44,45,[51][52][53][54]. Parks also significantly influence housing prices.…”
Section: Introductionsupporting
confidence: 65%
“…These include works by Boyce et al (1972), Dewees (1976), Lerman et al (1978), Dvett et al (1979, Damm et al (1980), Bajic (1983), Voith (1991, Al-Mosaind et al (1993), Gatzlaff and Smith (1993), Benjamin and Sirmans, (1996), Lewis-Workman and Brod (1997a;. Recently, researchers have also found positive effects of rail transports on house prices with between 0.1% to 39% increase in values for homes located near rail stations (Delmelle & Duncan, 2012;Pan et al 2014;Mulley et al, 2018;Dziauddin, 2019;Pan, 2019). Nonetheless, some studies have found rail transport's adverse effects on house prices.…”
Section: Rail Transport Impact On House Price and Rentmentioning
confidence: 99%
“…Dziauddin [39] Kuala Lumpur, Malaysia Condominium located within 800 m to light rail transit station valued $43,226 (30%) more compared to other parts of the city.…”
Section: Author Study Area Findingsmentioning
confidence: 99%